2021
DOI: 10.14742/ajet.6175
|View full text |Cite
|
Sign up to set email alerts
|

Accountability in educational dialogue on attrition rates: Understanding external attrition factors and isolation in online law school

Abstract: Australian higher education institutions have focused on attrition rates with increased vigour in light of the introduction of a new student success metric tied to attrition rates. Online programs have been of particular concern given persistently high attrition rates, being roughly double that of programs delivered either face-to-face or in blended online/face-to-face mode. This study considers attrition theory as it has evolved for the online environment with particular reference to the role of external risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Many students who had previous on-campus experience made comparisons of asynchronous OHE with face-to-face learning. OHE's absence of physical and temporal co-location with peers and instructors and the need to learn autonomously requires more time and effort, representing an important challenge of self-directed online learning (George et al, 2021). Being used to face-to-face learning and lacking prior OHE experience, learners struggled to adapt to the novelties and requirements of OHE-which takes time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many students who had previous on-campus experience made comparisons of asynchronous OHE with face-to-face learning. OHE's absence of physical and temporal co-location with peers and instructors and the need to learn autonomously requires more time and effort, representing an important challenge of self-directed online learning (George et al, 2021). Being used to face-to-face learning and lacking prior OHE experience, learners struggled to adapt to the novelties and requirements of OHE-which takes time.…”
Section: Discussionmentioning
confidence: 99%
“…Although online adult learners are more likely to be more independent and selfregulated, they suffer more from external factors such as life commitments than their younger counterparts (Lee et al, 2019). Non-traditional students often face an attrition risk trifecta (George et al, 2021): being mature and studying part-time and in online mode, they often struggle to conciliate four competing demands-study, family, work, and self. The transition to OHE, particularly the first semester, is especially relevant, as dropout occurs mostly during the first year, also affecting traditional students (Sánchez-Gelabert et al, 2020).…”
mentioning
confidence: 99%
“…This exploratory analysis of the user experience of teachers and students will be essential to inform further developments in the emerging area of VR in education. The ninth article focuses on the factors associated with attrition in an online law school in the Australian context (George, McEwan and Tarr, 2021). In particular, the authors were interested in how feelings of isolation had impacted the perceived strengths and challenges of online legal study.…”
Section: In This Issuementioning
confidence: 99%
“…While some have suggested that students primarily do not use it for academic purposes (Wise et al, 2011), the evolving functions of Facebook have led to it being studied as an educational tool for promoting collaboration (Chugh & Ruhi, 2018). Since it is already well integrated into many students' lives, the possibilities for communication and collaboration with other students are significant and George, McEwan and Tarr (2021) describe how a university developed Facebook site valuably supported some online students. However, student collaboration on Facebook might not be universally acceptable.…”
Section: Particular Technologies For Collaborationmentioning
confidence: 99%
“…To this end, computer supported collaborative learning (CSCL) has been established as a pedagogical approach (Feyzi Behnagh & Yasrebi, 2020). However, relative to face-to-face contexts, learners are more isolated in online spaces and therefore more likely to attrit (George et al, 2021). This is not simply a matter of who elects to study at distance as in the shift to online learning during the 2020 pandemic, students have described "feelings of disconnectedness and isolation from the group" (Hill & Fitzgerald, 2020, p. 3).…”
Section: Introductionmentioning
confidence: 99%